Respon Tanaman Bawang Merah (Allium Ascalonicum L.) Terhadap Jarak Tanam Dan Jenis Pupuk Organik - FLAVIANUS BUDIAS; I Gusti Bagus Udayana; , Anak Agung Ngurah Mayun Wirajaya (Fakultas Pertanian, Universitas Warmadewa, 2022)
Shallots are one of the commodities that are widely consumed by the public as a mixture of cooking spices. Shallots are also a medicinal ingredient to lower cholesterol levels, blood sugar, prevent blood clots, lower blood pressure and facilitate blood flow. In the world of agriculture,one effort to support the growth of shallots is by fertilizing, fertilization aims to add nutrients needed by plants, and can affect the physical properties, chemical properties, and biological properties of the soil . This study aims to determine the effect of planting distance and types of organic fertilizers on onion growth and production (Allium ascalonicum L.) This research is a field research conducted from March 2022 to June 2022 in Subak Rapuan, Mas Village, Ubud District, Gianyar Regency with a place height of 400 meters above sea level. This study is a factorial experiment using the Basic Design, namely the Group Randomized Design (RAK) which was tried to consist of two factors, namely the first factor is the planting distance (J) consisting of J1 (20 cm x 10 cm), J2 (20 cm x 15 cm) and J3 (20 cm x 20 cm). While the second factor is the type of organic fertilizer (P) which consists of rabbit manure 30 tons ha-1, chicken manure 30 tons ha-1 and cow manure 30 tons ha-1 . The results of this study showed that the interaction and treatment of spacing had an intangible effect on all observed variables. The treatment of organic fertilizer types has a marked to very noticeable effect on the treatment of plant height, number of leaves, number of tubers per clump, fresh weight of tubers and dry weight of tubers, while fresh weight of berangkasan, dry weight of the crop and harvest index have an unreal effect. The highest fresh weight and dry weight of tubers were obtained at a planting distance of 20 cm x 20 cm, namely 91.11 g and 20 cm x 15 cm, which was 20.42 g when compared to the lowest yield in the spacing treatment of 20 cm x 10 cm, an increase of 21.51% and 28.26%. The fresh weight of tubers and the highest dry weight of tubers tend to be obtained in the treatment of rabbit manure 30 tons ha-1, namely weighing 94.74 g and 23.00 g, when compared to the lowest yield in the treatment of chicken manure 30 tons ha-1, which weighs 67.51 g and 12.57 g, an increase of 40.33% and 82.97%.